Pembangunan kerangka pelaksanaan prinsip rekabentuk untuk pembuatan dan pemasangan ke arah pembinaan secara digital dan mampan di Malaysia - Afifuddin Husairi Hussain; Wan Hamidon Wan Badaruzzaman; Maria Zura Mohd Zain (Penerbit Universiti Kebangsaan Malaysia, 2023)
Industrialized building systems (IBS) have long been applied in Malaysia to increase construction productivity and reduced the dependency on unskilled foreign labourers. However, projects using IBS still face issues related to time and cost overrun, poor quality, and the dependence on unskilled foreign labours. This is mainly caused by less collaboration and low adoption of technology in project implementation. To enhance the performance of the construction industry, design for manufacturing and assembly (DfMA) principles were introduced. To add value to the DfMA principles, it is paired with the building information system (BIM) which would help in creating a sustainable digital environment in the construction industry. The main objective of this study is to look at the readiness of Malaysia’s construction industry to adopt the DfMA principles and develop a framework for it. This study builds a solid base from data collected from literature reviews. It is then progressed by interviewing several subject matter experts covering the perspectives of policymakers, developers, and IBS manufacturers. Based on thematic analysis, factors of people, processes, organization, and environment are identified. From these factors, a framework to adopt DfMA was formed. This study would assist the stakeholder in better understanding the DfMA principles and what is required to adopt them to exploit their potential to produce a sustainable construction in line with government policies on construction 4.0 and achieving the sustainable development goals. Based on this study, a better plan and strategy could be produced for a more competitive construction industry.